SMAD Signaling Is Required for Structural Integrity of the Female Reproductive Tract and Uterine Function During Early Pregnancy in Mice. Issue 2 (1st August 2016) - Rodriguez, Amanda; Tripurani, Swamy K.; Burton, Jason C.; Clementi, Caterina; Larina, Irina; Pangas, Stephanie A.
Abstract: Pregnancy is a complex physiological process tightly controlled by the interplay among hormones, morphogens, transcription factors, and signaling pathways. Although recent studies using genetically engineered mouse models have revealed that ligands and receptors of transforming growth factor beta (TGFbeta) and bone morphogenetic protein (BMP) signaling pathways are essential for multiple reproductive events during pregnancy, the functional role of SMAD transcription factors, which serve as the canonical signaling platform for the TGFbeta/BMP pathways, in the oviduct and uterus is undefined. Here, we used a mouse model containing triple conditional deletion of the BMP receptor signaling Smads ( Smad1 and Smad5 ) and Smad4, the central mediator of both TGFbeta and BMP signaling, to investigate the role of the SMADs in reproductive tract structure and function in cells from the Amhr2 lineage. Unlike the respective single- or double-knockouts, female Smad1 flox/flox Smad5 flox/flox Smad4 flox/flox Amhr2 cre/+ conditional knockout ( i.e., Smad1/5/4-Amhr2-cre KO) mice are sterile. We discovered that Smad1/5/4-Amhr2-cre KO females have malformed oviducts that subsequently develop oviductal diverticuli. These oviducts showed dysregulation of multiple genes essential for oviduct and smooth muscle development. In addition, uteri from Smad1/5/4-Amhr2-cre KO females exhibit multiple defects in stroma, epithelium, and smooth muscle layers and fail to assemble a closed uterine lumen upon embryo implantation, with defective uterine decidualization that led to pregnancy loss at early to mid-gestation. Taken together, our study uncovers a new role for the SMAD transcription factors in maintaining the structural and functional integrity of oviduct and uterus, required for establishment and maintenance of pregnancy.